Immune tolerance and the prevention of autoimmune diseases essentially depend on thymic tissue homeostasis - Shirafkan, Fatemeh; Hensel, Luca; Rattay, Kristin (Frontiers in Immunology, 2024)
The intricate balance of immune reactions towards invading pathogens and immune tolerance towards self is pivotal in preventing autoimmune diseases, with the thymus playing a central role in establishing and maintaining this equilibrium. The induction of central immune tolerance in the thymus involves the elimination of self-reactive T cells, a mechanism essential for averting autoimmunity. Disruption of the thymic T cell selection mechanisms can lead to the development of autoimmune diseases. In the dynamic microenvironment of the thymus, T cell migration and interactions with thymic stromal cells are critical for the selection processes that ensure self-tolerance. Thymic epithelial cells are particularly significant in this context, presenting self-antigens and inducing the negative selection of autoreactive T cells. Further, the synergistic roles of thymic fibroblasts, B cells, and dendritic cells in antigen presentation, selection and the development of regulatory T cells are pivotal in maintaining immune responses tightly regulated. This review article collates these insights, offering a comprehensive examination of the multifaceted role of thymic tissue homeostasis in the establishment of immune tolerance and its implications in the prevention of autoimmune diseases. Additionally, the developmental pathways of the thymus are explored, highlighting how genetic aberrations can disrupt thymic architecture and function, leading to autoimmune conditions. The impact of infections on immune tolerance is another critical area, with pathogens potentially triggering autoimmunity by altering thymic homeostasis. Overall, this review underscores the integral role of thymic tissue homeostasis in the prevention of autoimmune diseases, discussing insights into potential therapeutic strategies and examining putative avenues for future research on developing thymic-based therapies in treating and preventing autoimmune conditions.